A3.11 Induction of remission by low-dose IL-2-therapy in one SLE patient with increased disease activity refractory to standard therapies: A case report. (31st January 2014) - Humrich, J Y; von Spee, C; Rose, A; Siegert, E; Alexander, T; Hiepe, F; Burmester, G R; Riemekasten, G
Abstract : IL-2 deficiency and associated regulatory T cell (Treg) defects contribute essentially to SLE pathogenesis. In our previous translational work we proved the efficacy and safety of a low-dose IL-2 therapy in animal models and identified a reversible IL-2 deprivation of Treg also in human SLE patients, together providing the rationales for an IL-2-based immunotherapy of SLE in order to restore Treg activity and thus to re-establish endogenous mechanisms of tolerance that can counteract autoimmunity. Here we report for the first time that a repetitive and cyclic, subcutaneously applied, low-dose IL-2-therapy induced a rapid, strong and sustained reduction of disease activity in parallel to a remarkable and selective expansion of the Treg population in a SLE patient with increased disease activity (SLEDAI 14) refractory to a large variety of approved and experimental therapies. Already after the first therapeutic cycle, signs of arthritis and later also myositis and active skin eruptions disappeared. In addition, levels anti-dsDNA antibodies dramatically declined (ELISA) or even turned negative (Crithidia IFT). During the whole therapeutic regimen, the daily dose of glucocorticosteroids could be reduced from 30 mg/d to 10 mg/d, organ manifestations remained absent and disease activity remained low with a SLEDAI of 4 points. The therapy was very well tolerated and adverse events were minimal suggesting that this therapy is also very safe in SLE patients. In summary, these data provide the first evidence that a subcutaneous low-dose IL-2-therapy is capable to enhance Treg activity and to reduce disease activity in SLE patients, strongly supporting the rationales of this novel and pathophysiologically-driven therapeutic approach.